(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article analyzes the role of mother tongue education in human life, the level indicators of social emotional - civic competence that students in the DTS should possess across grades, and the problems in developing students’ social emotional - civic competences in mother tongue education and ways to overcome them.